Etching induced formation of interfacial FeMn in IrMn/CoFe bilayers. (12th February 2019) - O'Donnell, D; Hassan, S; Du, Y; Gauquelin, N; Krishnan, D; Verbeeck, J; Fan, R; Steadman, P; Bencok, P; Dobrynin, A N
Abstract: The effect of ion etching on exchange bias in IrMn3 /Co70 Fe30 bilayers is investigated. In spite of the reduction of saturation magnetization caused by the embedding of Ir from the capping layer into the Co70 Fe30 layer during the etching process, the exchange bias in samples with the same thickness of the Co70 Fe30 layer is reducing in proportion to the etching power. X-ray magnetic circular dichroism measurements revealed the emergence of an uncompensated Mn magnetization after etching, which is antiferromagnetically coupled to the ferromagnetic layer. This suggests etching induced formation of small interfacial FeMn regions which leads to the decrease of effective exchange coupling between ferromagnetic and antiferromagnetic layers.